PENGARUH CUSTOMER RELATIONSHIP MANAGEMENT TERHADAP LOYALITAS PELANGGAN PT. NASMOCO PEMUDA SEMARANG - Rizqa Janati Adnin; Nawazirul Lubis; Widayanto Widayanto (Universitas Diponegoro, 2013)
This study aimed to test the influence of Customer Relationship Management (CRM) on the customer loyalty of PT. Nasmoco Pemuda Semarang. The population of this study are 100 customers who use the repair shop service of PT. Nasmoco Pemuda Semarang. The author used SPSS 15.0 program to test the regression on the data analysis. And the study results indicates that CRM has a positive and significant influence on the loyalty customers, with the coefficient of determination is 46%. Results of this study indicate that in order to enhance the customer loyalty, PT. Nasmoco Pemuda Semarang should consider the CRM factors consisting of human resources, process and technology. Required intense interaction with the customers through the customer retention program, as well as good quality of customer service by the employees.